2016
DOI: 10.4236/fns.2016.73022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Shelf Life of Packaged Roast Beef and Some Treatments for Its Extension

Abstract: This study was carried out to investigate the effect of nitrite concentration, and abused chilling temperature against proper chilling temperature on the chemical, microbiological and shelf life of roast beef stored at 4˚C and 12˚C. Three roast beef treatments were formulated to investigate the effect of nitrite concentration (0.006%, 0.012% and 0.018%) and abused chilling temperature (12˚C) against control treatment (0.026% nitrite and storage at 4˚C) on the chemical, microbiological and shelf life. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In the case of fat content, there were significant differences among treatments (p≤ 0.05), where the highest value was in Tr1 (1.46%), followed by Tr3 (1.08%), and the remaining three treatments ranged from 0.77% to 0.86%. Results agreed with the findings of Maayah et al (2016) who reported 1.8% fat content in packaged roast beef.…”
Section: Proximate Analysissupporting
confidence: 91%
“…In the case of fat content, there were significant differences among treatments (p≤ 0.05), where the highest value was in Tr1 (1.46%), followed by Tr3 (1.08%), and the remaining three treatments ranged from 0.77% to 0.86%. Results agreed with the findings of Maayah et al (2016) who reported 1.8% fat content in packaged roast beef.…”
Section: Proximate Analysissupporting
confidence: 91%
“…When the roast beef Samples were compared with each other, the panelists were unable to differentiate sensory differences, despite of different added nitrite levels. These results indicate that the ability to extend shelf life of the roast beef [20] without affecting the sensory properties which are considered one of the main shelf life parameters. Moreover, storage and distribution of this product through the food chain could be enhanced and become more flexible.…”
Section: Sensory Evaluationmentioning
confidence: 80%
“…Therefore, we carried out the first part of this research to investigate the effect of different nitrite concentrations and chilling temperature on the shelf life and chemical parameters of the studied roast beef [20] and we found that roast beef containing 0.026% nitrite and stored at 4˚C for 25 days had the lowest thiobarbituric acid (TBA) values, microbial growth and the lowest percentage of nitrite losses during storage.…”
Section: Introductionmentioning
confidence: 99%